2019
DOI: 10.1016/j.joca.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The association between asymptomatic hyperuricemia and knee osteoarthritis: data from the third National Health and Nutrition Examination Survey

Abstract: Objective: In vitro and clinical studies suggest that urate may contribute to osteoarthritis (OA) risk. We tested the associations between hyperuricemia and knee OA, and examined the role of obesity, using a cross-sectional, nationally representative dataset. Method: National Health and Nutrition Examination Survey (NHANES) III used a multistage, stratified probability cluster design to select USA civilians from 1988 to 1994. Using NHANES III we studied adults >60 years, with or without hyperuricemia (serum ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
1
10
1
3
Order By: Relevance
“…A positive dose–response relationship between TC levels and the risk of KOA in clinical patients was demonstrated in a Chinese cohort [ 29 ]. In contrast, in other studies of the association between metabolic syndrome and OA, hyperlipidemia was not a risk factor for OA after adjusting for BMI and other factors [ 30 ]. We know that in the past, OA is generally considered to be a degenerative disease.…”
Section: Resultscontrasting
confidence: 57%
“…A positive dose–response relationship between TC levels and the risk of KOA in clinical patients was demonstrated in a Chinese cohort [ 29 ]. In contrast, in other studies of the association between metabolic syndrome and OA, hyperlipidemia was not a risk factor for OA after adjusting for BMI and other factors [ 30 ]. We know that in the past, OA is generally considered to be a degenerative disease.…”
Section: Resultscontrasting
confidence: 57%
“…[ 3 ] As for HU, four studies suggested a positive association with OA. [ 2 , 28 30 ] In contrast, only one studies reported that there was no association between gout and radiographic OA. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…The old age of the study population also limits conclusions with regard to the applicability of these results to other age categories, it may be limited to elderly females only, possible reasons being age-related changes in hand tissues and fluctuations in hydration status. The cut-off of SUA <372 μmol/L calculated in the current study may also vary between populations, depending on a number of other factors including obesity [14].…”
Section: Discussionmentioning
confidence: 99%
“…In rheumatology, hyperuricemia and symptomatic gout appear to be a part of a spectrum, with crystal deposition and synovitis in joints sometimes evident even in the absence of clinical gout [1113]. A recent NHANES study also indicates that hyperuricemia is associated with symptomatic knee osteoarthritis, most apparent in non-obese patients [14].…”
Section: Introductionmentioning
confidence: 99%